Biuletyn Informacyjny . no. 14, 1981 - MKZ NSZZ "Solidarność", [ed. board] (MKZ NSZZ "Solidarność", 1981)
Creation and circulation: Issues no. 1(16 XI 1980)-no. 52(27 XI 1981) published legally. From issue no. [1]=53(1 I 1982) to no. 120/121=172/173(1 VI 1989) journal published underground. Some issues destroyed by Służba Bezpieczeństwa, as noted in issue no. 100(1987). From issue no. 174(28 VI 1989) published again legally; In 1982-1983 with imprint: uncensored. Underground publication with fictitious addresses and names of print houses. In issue no. 100(1987) list of periodicals and books published underground in the Białystok region in 1982-1987.